Kirk-Othmer chemical technology of cosmetics - Kirk, Raymond E. 1890-1957; Othmer, Donald F. 1904-1995 (Wiley, 2013)
"Cosmetics and perfume represent a multibillion dollar global industry. Limited regulation and the enormous variety of ingredients make this comprehensive guide a valued resource for students and professionals in the field of personal care products. Based on Wiley's renowned Kirk-Othmer Encyclopedia of Chemical Technology, the book provides information on key product groups, ingredients, formulation technology, and related regulatory topics in 25 carefully selected articles. Chemists, R&D professionals, dermatologists, patent attorneys, and regulatory agencies will also benefit from this reference"--Vydavatelská anotace
"This volume contains carefully selected articles from Wiley's renowned Kirk-Othmer Encyclopedia of Chemical Technology, which have been updated and revised for this volume, as well as new contributions."--Z úvodu
Keywords: kosmetické přípravky; kosmetický průmysl; parfémy; chemická technologie; cosmetics; cosmetics industry; parfumes; chemical technology; monografie; monographs